2023
DOI: 10.1186/s12936-022-04436-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and therapeutic efficacy of artemether-lumefantrine in the treatment of uncomplicated Plasmodium falciparum malaria at Shecha health centre, Arba Minch, Ethiopia

Abstract: Background In 2004, Ethiopia adopted artemether-lumefantrine (AL, Coartem®) as first-line treatment for the management of uncomplicated Plasmodium falciparum malaria. Continuous monitoring of AL therapeutic efficacy is crucial in Ethiopia, as per the World Health Organization (WHO) recommendation. This study aimed to assess the therapeutic efficacy of AL in the treatment of uncomplicated P. falciparum infection. Methods A 28 day onearm, prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In Tanzania, AL were observed to have therapeutic efficacy of 98% which is the WHO recommended threshold and remain well tolerated in the country ( 96 ). The therapeutic efficacy of AL in Ethiopia was 98.6% (95% CI 92.3–100) for malaria infection, which suggests the continuation of AL as the first-line antimalarial drug for the treatment of uncomplicated plasmodium falciparum malaria in Ethiopia ( 97 ). Abacassamo et al assessed the clinical efficacy and parasitological response of Plasmodium falciparum to antimalarial drugs, he found that the therapeutic efficacy of 91.6% of amodiaquine (AQ) was better than that of 82.7% of sulphadoxine–pyrimethamine (SP) and 47.1% of chloroquine (CQ) to malaria infection ( 98 ).…”
Section: Discussionmentioning
confidence: 97%
“…In Tanzania, AL were observed to have therapeutic efficacy of 98% which is the WHO recommended threshold and remain well tolerated in the country ( 96 ). The therapeutic efficacy of AL in Ethiopia was 98.6% (95% CI 92.3–100) for malaria infection, which suggests the continuation of AL as the first-line antimalarial drug for the treatment of uncomplicated plasmodium falciparum malaria in Ethiopia ( 97 ). Abacassamo et al assessed the clinical efficacy and parasitological response of Plasmodium falciparum to antimalarial drugs, he found that the therapeutic efficacy of 91.6% of amodiaquine (AQ) was better than that of 82.7% of sulphadoxine–pyrimethamine (SP) and 47.1% of chloroquine (CQ) to malaria infection ( 98 ).…”
Section: Discussionmentioning
confidence: 97%